Dokumentarisme som funktion: En analyse af Thomas Ostermeiers iscenesættelse af En Folkefjende (2012) - Holm Mortensen, Johan (Peripeti, 2014)
Citing the notion of the author-function by Michel Foucault this article proposes a description of documentarism as a discursive function, presented by the staging in the relationship between the audience and discursive authority of the work. The documentarism of the staging of Henrik Ibsens An enemy of the people by Thomas Ostermeier is analysed from the perspective of the situation of address.